De novo [PSI +] prion formation involves multiple pathways to form infectious oligomers - Jaya Sharma (Nature Portfolio, 2017)
Abstract Prion and other neurodegenerative diseases are associated with misfolded protein assemblies called amyloid. Research has begun to uncover common mechanisms underlying transmission of amyloids, yet how amyloids form in vivo is still unclear. Here, we take advantage of the yeast prion, [PSI +], to uncover the early steps of amyloid formation in vivo. [PSI +] is the prion form of the Sup35 protein. While [PSI +] formation is quite rare, the prion can be greatly induced by overexpression of the prion domain of the Sup35 protein. This de novo induction of [PSI +] shows the appearance of fluorescent cytoplasmic rings when the prion domain is fused with GFP. Our current work shows that de novo induction is more complex than previously thought. Using 4D live cell imaging, we observed that fluorescent structures are formed by four different pathways to yield [PSI +] cells. Biochemical analysis of de novo induced cultures indicates that newly formed SDS resistant oligomers change in size over time and lysates made from de novo induced cultures are able to convert [psi −] cells to [PSI +] cells. Taken together, our findings suggest that newly formed prion oligomers are infectious.